2011
DOI: 10.1111/j.1365-3156.2011.02831.x
|View full text |Cite
|
Sign up to set email alerts
|

Can lay community health workers be trained to use diagnostics to distinguish and treat malaria and pneumonia in children? Lessons from rural Uganda

Abstract: Summaryobjective To determine the competence of community health workers (CHWs) to correctly assess, classify and treat malaria and pneumonia among under-five children after training.methods Consultations of 182 under-fives by 14 CHWs in Iganga district, Uganda, were observed using standardised checklists. Each CHW saw 13 febrile children. Two paediatricians observed CHWs' assessment, classification and prescription of treatment, while a laboratory scientist assessed CHW use of malaria rapid diagnostic tests (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
141
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(161 citation statements)
references
References 38 publications
16
141
4
Order By: Relevance
“…15 While this may have resulted from ongoing training and mentoring related to the mRDT and rectal artesunate project, it also illustrates that, when they are appropriately trained, community-level CHWs can deliver services of comparable quality to those delivered by facility-level health workers. 20 There were some limitations for this study; first, although the findings of this study suggested a significantly high clinical response to only antipyretics for children who were mRDT-negative, it is possible that some parents or guardians might have given their sick children medications sourced elsewhere, which might have had an effect on the outcome of the study. Although all enrolled children reportedly did not receive antimalarials within 14 days prior to enrolment, there was no way of corroborating this information.…”
Section: Discussionmentioning
confidence: 82%
“…15 While this may have resulted from ongoing training and mentoring related to the mRDT and rectal artesunate project, it also illustrates that, when they are appropriately trained, community-level CHWs can deliver services of comparable quality to those delivered by facility-level health workers. 20 There were some limitations for this study; first, although the findings of this study suggested a significantly high clinical response to only antipyretics for children who were mRDT-negative, it is possible that some parents or guardians might have given their sick children medications sourced elsewhere, which might have had an effect on the outcome of the study. Although all enrolled children reportedly did not receive antimalarials within 14 days prior to enrolment, there was no way of corroborating this information.…”
Section: Discussionmentioning
confidence: 82%
“…Correct interpretation was high for the direct assessment of RDTs; 96 to 100% of tests and 95.1 to 100% of CHWs, provided that CHWs were trained properly [18,19,21,32]. In photographic assessments, which have the inherent risk of selection bias as the number of ambiguous tests is relatively high, well-trained CHWs also scored high numbers of correctly interpreted tests, although more mistakes were made in reading faint positive and invalid tests [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…The way CHWs executed RDTs was judged on several items, but differences in number and definition of items further impaired comparison [18-21,32]. Nevertheless CHWs were found to correctly conduct RDTs if properly trained; 90 to 100% of steps were successfully executed in two studies that used the same WHO checklist, Hawkes et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies conducted in Africa have shown that RR assessed by CHWs is inaccurate 10 11. In a recent Ugandan study, CHWs counting the RR resulted in correct diagnosis and treatment of only 40% of all cases of childhood pneumonia 11. An instrument to facilitate accurate RR measurement at the village level could improve pneumonia diagnosis and case management.…”
Section: Introductionmentioning
confidence: 99%